Influência da população idosa feminina na avaliação de conforto térmico pelo Modelo de Fanger - Ruviaro, Raiana Spat (2018)
On the world stage, the age pyramid have been suffering alterations with the accelerated increase of aged people, which characterizes the aging of global population. Therefore, it is necessary to create conditions for aged people to live in well-being, physical and mental health as well as to provide life quality improvements. Thermal comfort has essential contributions for a human and accessible architecture. Thus, the present work intends to contribute with the theme from the analysis of the influence of the elderly female population in the evaluation of thermal comfort by the Fanger method, normalized by ASHRAE and ISO, in living environments of two long stay nursing homes in the city of Santa Maria, RS. The target audience considered for this work was female person aged 60 years or older. The environmental variables of air temperature, humidity, globe temperature and air velocity as well as the human variables of clothing insulation and physical work have been collected. The research also measured the thermal sensation and preference of the elderly women by means of the application of surveys, to evaluate their thermal perception. After the data collection, the indices for sensation of thermal comfort were calculated, as the predicted mean vote (PMV) and the predicted percentage of dissatisfied (PPD). The data analysis was descriptive and comparative of the field research information and the indices determined by the PMV model. The PMV and PPD were related with the real sensation of the researched population to verify the mutual relation established between the indices, to demonstrate how the model explains or not the results collected. The main result is that the PMV model is applicable, with reasonable accuracy, to evaluate the thermal comfort considering the researched population. However, there is a tendency for the elderly women to feel slightly more heated then the model estimates. It is highlighted the importance of metabolic rate calculation for each person considering the weight, height and age for the PMV model application in terms of studies applied to elderly women in Santa Maria, RS because the alteration of this variable results in significantly different outputs, obtained by the metabolic rate accuracy verification. Additionally, the study established the thermal comfort limits for the elderly women researched by statistical analysis, considering the air temperature and humidity limits of the tree rooms researched, resulting in a mean comfort range with internal air temperature of the rooms between 21,68ºC and 24,81ºC and internal relative humidity between 44,33% and 72,52%.